CONSTRUCTIVIST ANALYSIS OF STUDENTS’ MULTIMODAL TEXTS INTEGRATING LOCAL WISDOM IN THE DIGITAL LITERACY ERA - Maulana, Nanang; Hidayat, Sholeh; Anriani, Nurul (Universitas Islam Sumatera Utara (UISU), 2025)
This study aims to analyze university students’ multimodal texts that integrate local wisdom values through the lens of Jean Piaget’s constructivist perspective. The study connects constructivist theory with digital literacy practices rooted in local culture, an area that remains underexplored in Indonesian language education. The research employs a descriptive qualitative approach, focusing on the process of students’ knowledge construction in producing multimodal texts based on local wisdom. The participants were third-semester students of the Indonesian Language, Literature, and Regional Education Program, Faculty of Teacher Training and Education, Mathla’ul Anwar University, Banten. The primary data consisted of multimodal text products themed around the local wisdom of Pandeglang, while supporting data were obtained through direct classroom observations and semi-structured interviews. The research instruments included observation sheets, interview guides, and students’ reflection journals. The data analysis process was guided by Piaget’s constructivist framework, which examined the processes of assimilation, accommodation, and equilibration in students’ cognitive development. Data were analyzed through three stages: data reduction, data display, and conclusion drawing, with triangulation employed to ensure data credibility. The findings reveal that students actively assimilated local wisdom knowledge with academic theory, adjusted their ways of thinking and presenting cultural values in multimodal texts, and achieved a balance between cultural preservation and the demands of digital literacy. The process of creating multimodal texts also demonstrated experiential learning (learning by doing) and self-reflection, while variations in visual and narrative styles reflected each student’s individual knowledge construction.